SOCIAL CHANGE IN LOCAL PERSPECTIVE: WILD ANIMAL QANUN AND ELEPHANTS IN CRU ACEH, INDONESIA - Iklila H, Khansa; Alamulhuda H, Agha; Rifa’i Q, Muhammad; Rakata F, Suha; Anuan F, Maisan; Lathifa, Zhafiratul; Ulfa, Maria; Gagarin, Yuri; Abdullah, Abdullah; Zulfikar, Zulfikar; Wahid, Ikhlas; Rusnawati, Rusnawati (Jurnal Belantara, 2025)
Social changes in a society can help provide information related to that society. Qanun is a statutory regulation or a kind of regional regulation that regulates the life of the Acehnese people. This study aims to determine the social changes that occurred in Ie Jeureungeh Village. In addition, to find out the understanding of the residents of Ie Jeureungeh Village towards the wildlife Qanun. The benefits of this research are to provide information, add insight and knowledge. This research was conducted using descriptive qualitative method and focal animal sampling. The research subjects were 24 people with the technique of taking using purposive sampling technique. The study to determine the social changes that occurred in Ie Jeureungeh Village used 3 factors, namely, causative factors, pushers and inhibitors. The results showed that there were social changes that occurred in Ie Jeureungeh Village, and the people of Ie Jeureungeh Village tended to know about the wildlife Qanun.